Model Based Ultrasonic Measurement Technique for Evaluation of the Adhesive Properties - Liaukonis, Dobilas; Mazeika, Liudas; Barauskas, Rimantas; Neciunas, Audrius (Elektronika ir Elektrotechnika, 2018)
The adhesive joints are common technique to joint different types of material such as metal to composite, composite to composite and etc. However, quality assessment of such joints is essentially more complicated comparing for to welds. Except problems related to presents of few materials with the completely different properties there is additional task of evaluation of the quality of cured adhesive. Usually joint defect are classified into the adhesive (bad adhesion between material and adhesive) and cohesive (defect in the layer of adhesive). Most of researcher’s main attention is paying to the analysis of adhesive defects. Cohesive problem is more complicated and investigated essentially less. The key problem in this case is the fact that not some delamination should be detected, but the material properties of the thin layer of adhesive after curing should be evaluated. For solution of this task the model based ultrasonic measurement technique was proposed and investigated. According to this method, the frequency dependent attenuation is estimated and compared with attenuation obtained by Combined Maxwell and purely viscous model. The method was demonstrated investigating several samples of cured adhesive. DOI: http://dx.doi.org/10.5755/j01.eie.24.5.21840